Impacts and savings of energy efficiency measures: A case for Mexico's electrical grid. (15th March 2022) - Ramirez-Sanchez, Edgar; Evangelista-Palma, Gabriel; Gutierrez-Navarro, Daniel; Kammen, Daniel M.; Castellanos, Sergio
Abstract: In the efforts to decarbonize the electricity sector, energy efficiency approaches have consistently shown co-benefits that merit investment and further development. Tools that can help decision-makers evaluate the economic and environmental impacts could accelerate the adoption of energy efficiency measures and support the development of targeted incentives, both spatial and temporally. In this work, a unified, corrected, and high-resolution electricity consumption framework is first developed to produce new data insights with an increased spatial and temporal resolution, allowing the possibility of performing detailed energy policy scenarios. A case scenario for Mexico is constructed, where the impacts in the electrical grid from a suite of energy efficiency measures are quantified at high spatial and temporal resolution. The novel data sets are used to model electricity-reduction approaches in great detail for the most electricity-consuming economic activities in the country. It is shown that commercial electricity consumption is underestimated by up to 3 × in government reports and that US$ 11B could be saved in the wholesale electricity market —equating to 142 MtCO2eq of avoided emissions— if a 12% electricity reduction target is implemented to the top-20 most demanding economic activities over the years 2021–2035. Potential priorities for incentives are identified based on criteria suited for different stakeholders, including economic and environmental justice dimensions. Highlights: A framework to address energy data gaps in emerging economies is introduced. Novel energy data sets are constructed at high spatial and temporal resolution. Applied to Mexico, 3x commercial electricity consumption differences are revealed. Energy efficiency measures in Mexico could save up to US$ 11B. Energy efficiency in Mexico can reduce 18.5% of INDC emissions by 2030.